A re‐analysis that supports our main results: A reply to Levine et al. (4th November 2017) - Vrij, Aldert; Blank, Hartmut; Fisher, Ronald P.
Abstract : Levine et al . (2018) criticized our meta‐analysis, but their conclusion was the same as ours: The cognitive approach to lie detection results in a modest improvement. We address and dismiss Levine et al .'s (2018) three criticisms. Regarding the 'confound', in our meta‐analysis we averaged the results of two cells on statistical grounds, which does not constitute a confound in statistical terms. Regarding 'aberrant controls', that depends entirely on the benchmarks selected and type of statistical test and meta‐analysis used. Regarding 'unreliable data', the claim that there is a positive relationship between 'unreliable' data and total accuracy in the cognitive lie detection conditions is not even supported by their own data ( p  =   .16). We conclude with a request to Levine et al . to focus on our shared aim: to develop interview protocols that enable lie detection.